Groundwater potential in a drought prone Betwa river basin, Bundelkhand - JEET, PAWAN; SINGH, D K; SARANGI, A (The Indian Journal of Agricultural Sciences, 2019)
This study presented a modified concept of assessing groundwater potential and water table level behavior under varying rate of recharge potential for regional scale modeling of Betwa basin using Processing ModFlow for Windows model. Betwa basin of Bundelkhand region which covered the districts of Madhya Pradesh and Utter Pradesh was selected to apply this concept. The model was calibrated and validated using observed water table elevation data for the period 2005–2013, which showed agreement between observed and predicted water table elevation. The coefficient of determination (R2) ranged between 0.74–0.87 for calibration and 0.63–0.87for validation. Scenario analysis represents the water table elevation under three varying groundwater recharge condition in Shahijina, Garrauli, Mohana and Basoda sub-basin of Betwa basin. Results shows that the scenario based on recharge with 60% of surface runoff combined with river bed recharge and natural recharge has maximum influence on groundwater recharge. Groundwater recharge under the scenario varied from 0.33–1.61 m above reference level. Recharge from 30% of surface runoff combined with river bed recharge and natural recharge varied from 0.16–1.05 m above reference level. The study shall be useful for planning of groundwater development in Betwa basin and to suggest an alternate location for development of soil and water conservation structure. The water table elevation simulation also showed that the recharge levels and the sustainability of groundwater resources cannot be ensured unless water availability in arid to semi-arid region river basin increased.